Clinical determinants of neurologic worsening in various stroke subtypes - N. V. Oleksyuk; V. V. Zudin; M. A. Sychyova; Yu. T. Kouryachenko (Бюллетень сибирской медицины, 2008)
With the purpose of clinical determinants definition of neurological deterioration in patients with an ischemic stroke and its prognostic value, the retrospective analysis of case records of 253 patients with first in a life stroke was carried out and the estimation of neurological deterioration of early period of an stroke was performed.